On Translation Studies in Romania - PETRARU, Ana‐Magdalena (2022)
This book is the result of our research conducted in the field ofTranslation Studies since our undergraduate years at the Faculty ofLetters where we majored in English and minored in French between2001-2005. Our bachelor thesis title was The Translator’s Notes, hence asubchaper devoted to the topic. Special thanks, in this regard, are owedto professor Rodica Dimitriu, former Head of the English Department atAlexandru Ioan Cuza University of Iași for her guidance throughout ourentire academic formation (undergraduate and postgraduate years) ascoordinator of our Bachelor, MA and doctoral theses. We devoted ourMA dissertation to the translation of comics and, consequently, weincluded a subchapter on it in our study, focusing on some Romanian andEnglish versions of Herge’s Tin Tin that we have also dealt with in thepast. Last but not least, during our postdoctoral fellowship (2014-2015)we studied the Romanian discourse on translation, so most of this bookis a collection of revised papers that came out then or in the followingyears.